Sunda Empire dalam Era Post-Truth: Misinformasi, Psikologi Kepercayaan Publik, dan Implikasinya terhadap Demokrasi Indonesia - Widhya Facitha Rezaliany; Tiara Tahta Anindhita; Ali Ridho; Saffiya Hisaan Irhamna Pranowo; Arofah Minasari (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2026)
This study examines the phenomenon of the Sunda Empire as a socio-political phenomenon in the post-truth era, highlighting how public trust can be formed in pseudo-historical claims and its impact on the quality of democracy in Indonesia. This study uses a qualitative approach through a literature review modified from a systematic literature review framework to thematic analysis and discourse analysis, with sources consisting of scientific journals, reports, public documents, credible news, and relevant social media content. The synthesis results show that the Sunda Empire builds pseudo-legitimacy through narrative repetition, the use of symbols of authority, a formal communication style, and the exploitation of the social media ecosystem that accelerates virality. The findings also show that public acceptance is influenced by psychological mechanisms such as the illusion of truth effect, the need for identity, and the tendency to trust familiar and emotional information. The implication is that the vulnerability of information and political literacy can weaken public deliberation, increase the space for misinformation, and erode trust in democratic institutions. This study emphasizes strengthening information literacy, media literacy, and political literacy through formal education, community programs, and collaboration with digital platforms as a strategy for democratic resilience in the post-truth era.